PEMINJAMAN LEKSIKAL DAN VARIASI MORFOSINTAKSIS PADA KOMUNITAS TUTUR MELAYU DI WILAYAH PERBATASAN INDONESIA–MALAYSIA - Hasanah binti Zakarya Ali; Amzar Ghazali Noordin; Aziz Damar Putra (UNIVERSITAS PGRI YOGYAKARTA, 2025)
This study examines lexical borrowing and morphosyntactic variation in cross-border Malay speech communities along the Indonesia–Malaysia border, focusing on Entikong–Tebedu and Nunukan–Tawau. It aims to identify patterns, types, and levels of integration of borrowed lexical items and to analyze structural variation arising from sustained language contact. A mixed-methods design is employed, combining quantitative corpus analysis with qualitative sociolinguistic interpretation. The dataset includes 20–30 hours of naturally occurring spoken interactions, supported by interviews and digital communication data. Participants (n = 40–60) were selected to represent diverse sociolinguistic backgrounds. The findings show that lexical borrowing is pervasive, accounting for approximately 38% of lexical items in domain-specific discourse, particularly in trade and administrative contexts. Borrowings originate mainly from Indonesian, Malaysian Malay, and English, and are realized as loanwords, calques, and hybrid forms, with loanwords being the most dominant. Evidence of morphosyntactic integration is reflected in the use of local affixes attached to borrowed roots. Morphosyntactic variation is observed in affixation, word order, and clause structure, indicating ongoing convergence between Indonesian and Malaysian Malay varieties. Statistical analysis reveals that cross-border mobility is the strongest predictor of linguistic variation, followed by age and occupation. Younger and highly mobile speakers demonstrate greater use of innovative and hybrid forms. The study contributes to contact linguistics by offering empirical insights from a transnational context and highlighting the interaction between lexical and structural change. The findings underscore the role of social and functional factors in shaping language practices in multilingual border communities.